Doc Martin. Series 7 [videorecording (DVD)] - Clunes, Martin, 1961-; Catz, Caroline (Acorn, 2015)
In these all-new episodes, the doctor continues his practice in the picturesque seaside town of Portwenn, while raising his son with wife Louisa.